2018
DOI: 10.4103/ijnmr.ijnmr_105_16
|View full text |Cite
|
Sign up to set email alerts
|

The effect of auriculotherapy on the stress and the outcomes of assistant reproductive technologies in infertile women

Abstract: Background:Infertility means failure to achieve pregnancy after one year of regular unprotected sexual intercourse. Infertile women may experience severe stress and depression. Numerous studies have indicated that auriculotherapy could reduce stress. Thus, the aim of the present study was to determine the effect of auriculotherapy on the stress and the outcome assisted reproductive technology in infertile women.Materials and Methods:The present study was a clinical trial that was conducted on 56 infertile wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
(38 reference statements)
0
6
0
1
Order By: Relevance
“…After the evaluation, it was observed that the group whose technique used needles obtained better results in comparison with the other options, nevertheless, the authors recommend the use of seeds to generate less discomfort and to allow the application by trained people, when a protocol is to be used. It is inferred, therefore, that this is the reason for the researchers 21,25 to use seeds in their interventions. Study 1 used both needles and seeds, and the study 3 used only needles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the evaluation, it was observed that the group whose technique used needles obtained better results in comparison with the other options, nevertheless, the authors recommend the use of seeds to generate less discomfort and to allow the application by trained people, when a protocol is to be used. It is inferred, therefore, that this is the reason for the researchers 21,25 to use seeds in their interventions. Study 1 used both needles and seeds, and the study 3 used only needles.…”
Section: Resultsmentioning
confidence: 99%
“…Another factor that may interfere with research results and depends on the participants of the sample is the stimulation of auricular points in which seeds were applied, they need to be pressed for better results and the researchers as not able to find out if this action was actually performed by the participants. 22,[24][25] Placebo effect was one aspect that influenced the results. Due to varied situations, this term was frequently cited by the researchers in the study limitations section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, acupressure and improving endocrine function can help regulate hormones and reduce mental disorders in patients with PCOS. Correspondingly, Valiani et al revealed that auriculotherapy reduces stress and improves fertility treatment [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Auriculotherapy (treatment through the ear) is a type of acupuncture that has become a separate and unique alternative treatment method in the last 60 years and was officially recognized by the WHO in 1990 [ 14 , 15 ]. Ear acupuncture can reduce the pleasure of eating and the feeling of hunger [ 16 ] and increase the feeling of satiety [ 17 ].…”
Section: Introductionmentioning
confidence: 99%